Institutional Theatrics Performing Arts Policy in Post-Wall Berlin - Woolf, Brandon (Book collections on Project MUSE., 2021)
"Since the fall of the Berlin Wall, political and economic agendas in the reunified German capital have worked to dismantle the state-subsidized stage. Institutional Theatrics charts the ways artists have reimagined the theater in response to these crises"--